Survei Minat Siswa Terhadap Pembelajaran Online Siswa Kelas VI SDN Wonokusumo V Surabaya Di Tengah Pandemi Covid-19 - Fajar Albana; Fajar Setiawan; Kunti Dian Ayu Afiani (STKIP Andi Matappa Pangkep, 2021)
This article aimed to inform students' interest in participating in online learning during the Covid-19 pandemic in sixth grade SDN Wonokusumo V/44 Surabaya. During the Covid-19 outbreak, student interest in learning is different. This type of research used a qualitative descriptive survey. The subjects of this study were teachers, parents of students, and sixth-grade SDN Wonokusumo V Surabaya. This study used data triangulation with questionnaires and interview guidelines. The data were analyzed using qualitative descriptive analysis techniques. The results of this study indicated that there were obstacles to online learning experienced by students, lack of effectiveness of online learning, and decreased student interest in learning amid the COVID-19 pandemic.